Cell-to-cell modeling of the interface between atrial and sinoatrial anisotropic heterogeneous nets. (June 2017) - López Garza, Gabriel; Castellanos, Norma P.; Godínez, Rafael
Abstract : Graphical abstract: Abstract : Highlights: Geometry is relevant in the SA transitional zone conduction paths. Conductance values can not be used as free parameters. The sum of conductances of an entire net is a bifurcation parameter. Abstract: The transition between sinoatrial cells and atrial cells in the heart is not fully understood. Here we focus on cell-to-cell mathematical models involving typical sinoatrial cells and atrial cells connected with experimentally observed conductance values. We are interested mainly in the geometry of the microstructure of the conduction paths in the sinoatrial node. We show with some models that appropriate source-sink relationships between atrial and sinoatrial cells may occur according to certain geometric arrangements.